ECMO support for right main bronchial disruption in multiple trauma patient with brain injury—a case report and literature review. (July 2015) - Zhou, R; Liu, B; Lin, K; Wang, R; Qin, Z; Liao, R; Qiu, Y
Extracorporeal membrane oxygenation (ECMO) may offer life-saving treatment in severe pulmonary contusion or acute respiratory distress syndrome when conventional treatments have failed. However, because of the bleeding risk of systemic anticoagulation, ECMO should be performed only as a last resort in multiple trauma victims. Here, we report ECMO as a bridge for right main bronchus reconstruction and recovery of traumatic wet lung in a 31-year-old male multi-trauma patient with right main bronchial disruption, bilateral pulmonary contusion, cerebral contusion and long bone fracture. The patient was discharged without any obvious complication. ECMO support in a traumatic brain injured patient with severe hypoxemia caused by lung contusion and/or tracheal bronchus disruption is not an absolute contraindication.